Peran Pembimbing Kemasyarakatan Bapas Dalam Penanganan Perkaran Anak - Salvadoris Pieter; Herry Hendri Fernando Mote; Raymond Paradeys Fenetiruma (Jurnal Restorative Justice, 2024)
This study aims to determine the role of Social Counselors and find out the obstacles faced. This research is empirical legal research. The results of the research show that the duties of the Community Counselor are conducting community research, mentoring, mentoring, and supervising children in every criminal justice examination process, namely the pre-adjudication stage, namely investigation, the adjudication stage, namely assistance in post adjudication trials, namely supervision and guidance for children who conflict with the law. Obstacles faced by Community Counselors are a) The rule of law does not yet have strict sanctions if there are violations committed by law enforcers, b) facilities and infrastructure that are still inadequate, c) the work area is very wide) d) coordination between law enforcers who other with Correctional Centers that are still not running well, e) limited budget allocations.